Metric Type II Bursts with and without Coronal Mass Ejection During 20 Years - Mohammed , Mohammed A.; Abood , Kamal M.; Alsawad , Amjad A. (Iraqi Journal of Science, 2021)
Metric type II bursts are formed from shocks driven by CME or flares which isindicative of particles (SEPs) accelerated to high energies. This work aims toinvestigate the metric type II bursts, CMEs and flare for twenty years (1996-2016,inclusive) over two solar cycles 23 and 24. The total metric type II bursts was 1378events divided into two groups: first group associated with CMEs regardless theirproperties and this group has (1147) events. The second group associated with flareswhich has (231) events. The interstice fraction of this research is the metric type IIassociated with CME is 83% whereas only 17% with flare where this very close tothe previous study in 2005 which found 81% despite it was for only six years. Thisagreement between the two studies may lead to there are a regular emission ofCMEs and flares over long periods.